Experimental assessment and semi empirical estimation of frost accretion—A case study on a spine-finned inverted-V tube array evaporator - Carvajal-Mariscal, I.; De León-Ruiz, J. E.; Belman-Flores, J. M.; Martínez-Espinosa, E.; José-Pineda, O. (Frontiers in Mechanical Engineering, 2023)
Present work focuses on frost accretion in a spine-finned inverted-V tube array evaporator. An experimental evaluation was performed using a standard issue, vertical top-mount, 18 cubic feet, 0.5m^3, refrigerator. Evaporator temperature distribution, inner airflow velocity, and relative humidity were measured to account for convective phenomena influencing frost distribution. Frost formation and accretion on the surface of the evaporator were visualized using thermal and microscopic imagery. The images were processed using a machine vision algorithm to measure frost thickness. Complementarily, frost density and vapor mass transfer were computed using available correlations. An estimation function was derived from the compiled data using direct measurements and thermophysical substance properties. The resulting mathematical expression estimated the frost accretion rate within an error expectancy, RMSE, of 0.1479 and displayed a goodness-of-fit, R-Squared, of 0.9029. Based on these results, the estimation function derived, is proposed as a viable approach to construct adequate limits for new predictions, vis-à-vis evaporator performance, ultimately reducing appliance energy consumption via implementing more effective control strategies regarding internal defrosting.